In the transitions from novel to drama (“Killed Dove” by Nar-Dos) - Jrbashyan, Ashkhen (Bulletin of Yerevan University B: Philology, 2024)
The purpose of this article is to use the example of Nar-Dos’ novel and drama “The Killed Dove” to show the transformation of narrative discourse into dramatic discourse, to present the changes in the source text at different formal and content levels - event, composition, plot, narrative, etc. Discussed material is also interesting, because the transition from novel to drama was carried out by the same author; in this regard, the change in narrative focalization follows exclusively from the characteristics of dramatic discourse. Transformation from the genre of novel to drama involves a transition, in other words, a “translation” from one text system to another, as a result of which changes in ideological and thematic accents, the removal of “untranslatable” elements, plot distortions and some weakening of the impact of the source text become regular. The transformation of the novel “The Killed Dove” into drama has occurred chronotopic changes, the actions are significantly pressed, spatial coverage also underwent serious changes caused by the possibilities of the stage and the limitations of dramatic time. The arrangement of episodes at the compositional and plot level has also changed significantly. However, the most serious loss is perhaps at the narrative level, where the dominant point of view has been replaced by polyphonism. At the linguistic level dialectisms and colloquial elements are included in the text. In our opinion, as a result of such a genre change, the literary text has significantly weakened and lost its psychological depth.